The Role of Traditional Leaders in Bridging Cultural Values - Yusni Khairul Amri; Dian Marisha Putri (Britain International for Academic Research (BIAR-Publisher), 2023)
The role of Angkola Mandailing traditional figures as representatives of the cultural values ​​laid down by their ancestors in an effort to regenerate the sustainable values ​​of Angkola Mandailing customs and culture is increasingly being eroded, this is where it is important to strengthen the role of Angkola Mandailing traditional figures. wise and wise values ​​such as: a) maintaining human relationships with God, b) maintaining the meaning of human life, c) maintaining human relationships with the natural environment, d) maintaining human relationships with time, e) maintaining active, frugal and religious behavior, harmony one another; f) maintain the value of humility, politeness customs, g) giving traditional messages as advice in that the marriage will become a lifelong marriage; h Explain the philosophical meaning of ingredients used in ceremonies that come from animals, plants and come from nature; i) advise and encourage the bride and groom to maintain customs. The role of the Dalihan Na Tolu traditional figure is as a form of affection by maintaining relationships with social interactions between mora, kahanggi, and anak boru who are bound by the rights and obligations of one another in the Dalian na Tolu customary and cultural order. Dalihan na tolu traditional figures play a role in giving advice to maintain friendly relations and stay close. Related families have been recommended since the beginning of marriage, so that we know each other about who our relatives are.